The Empowerment of Households towards Independence through Social Capital in Program Keluarga Harapan (PKH): Pemberdayaan Rumah Tangga menuju Kemandirian melalui Modal Sosial pada Program Keluarga Harapan (PKH) - Lestari, Widia; Kartono, Drajat Tri; Demartoto, Argyo; Setiyawan, Khabib Bima (Society, 2019)
This research aims to reveal 1) The Role of Program Keluarga Harapan or known as PKH (Family of Hope Program) in empowering beneficiary households or known as KPM (Keluarga Penerima Manfaat), 2) The Role of Social Capital in realizing the independence of KPM-PKH in Sukoharjo district, Central Java Province, Indonesia. This research was qualitative by using a case study approach. The determination of informants used a purposive sampling technique. The informants were eight beneficiary households and four key informants they were the Head of Sukoharjo district office of the Ministry of Social Services, coordinator of Sukoharjo district, PKH supervisor, PKH facilitator, and two key informants to support any information. Data were collected through observation, interviews, and documentation. The data were analyzed into three stages; data reduction, data display, and conclusion drawing. The data were verified by observation and source triangulation and time. The result showed that 1) The Role of PKH in empowering the beneficiary households by providing social assistance, strengthening by the regular meeting of Family Development Session, known as P2K2 (Pertemuan Peningkatan Kemampuan Keluarga), strengthening by PKH cooperative, and joint business group, known as KUBE (Kelompok Usaha Bersama), 2) The Role of social capital to build independence of KPM-PKH by adopting cultural values, trust, reciprocity, participation, communication system, and venture networks of beneficiary households. This is caused by the relevance of social bonding, social bridging and social linking carried out by KPM-PKH. To conclude, livelihoods choice of KPM-PKH by employing social capital becomes strategic and productive opportunities to empower independence among poor households as beneficiary of PKH.